Microstructural and wear properties of the Al-B4C composite coating produced by hot-press sintering on AA-2024 alloy - Ozay, C.; Ballikaya, H.; Dagdelen, F.; Karlidag, O. E. (Korean Soc Mechanical Engineers, 2021)
In this study, the surface of an AA-2024 alloy was covered with reinforced composite coating using hotpress sintering method. Al and B4C powders were synthesized through mechanical alloying technique and coated on the AA-2024 substrate at different rates. The microstructure of the intermediate transition region formed between the substrate (AA-2024 Al alloy) and the coating layer (Al/B4C MMCs), the microstructure of the Al/B4C metal matrix composites (MMCs) coating, the microhardness, and the adhesive wear resistance of the Al/B4C MMCs coating layer were investigated. It was observed that B4C powders homogeneously dispersed in the microstructure of the Al/B4C MMCs coating layer, moreover, the Al matrix and B4C reinforcement particles were bonded without a gap. It was also determined that an interface bonding occurred between Al/B4C MMCs coating layer and the AA-2024 substrate. Accordingly, it was determined that with the increase of B4C reinforcement particle ratio, the hardness of the coating layer, and the wear resistance increased.
Keywords: Hot press sintering; Al-B4C coating; Wear; MMCs